A preliminary assessment of energy consumption behaviour pattern and factors influence among malaysian higher education institutions students - Ishak, M.H.; Sipan, I.; Mar Iman, A.H.; Sapri, M. (Penerbit UTM Press, 2015)
Towards sustainable campus of higher education institutions (HEIs), energy consumption behaviour is one of the several matters that require attention by the facilities manager. Information on energy consumption behaviour helps on developing a good strategy for energy management. The purpose of this study is to assess energy consumption behaviour among Malaysian HEIs student. This study has an objective to determine energy consumption patterns and analyse the factors that influence the pattern. The ‘energy culture’ framework consolidated with ‘centrographic’ approach and econometric analysis used to strengthen the findings. A self-administrated survey carried out involving 158 respondents in Universiti Teknologi Malaysia, Johor. There are three types of energy use among students in HEIs namely, ‘high’, ‘low’, and ‘conserve’. The ‘device’, ‘activities’ and ‘building regulation’ are the influence factors on the pattern of energy